Improving Collaboration in Higher Education Through ChatGPT Using the Addie Framework - Mabina, Alton (COMPETITIVE: Journal of Education, 2025)
The integration of artificial intelligence (AI) in higher education has gained significant attention, particularly in enhancing collaborative learning. This study explores the effectiveness of ChatGPT in improving group interactions, critical thinking, and engagement using the ADDIE framework. The research provides a structured approach to AI adoption, ensuring it complements traditional teaching methods rather than replacing them. A systematic review of AI-supported educational frameworks was conducted, analyzing studies from academic databases. Inclusion criteria focused on research involving AI-assisted collaborative learning, while exclusion criteria omitted studies unrelated to higher education or lacking empirical evaluation. Results indicate that while models like Bloom’s Taxonomy, TPACK, and SAMR contribute to AI-enhanced learning, they lack structured implementation for collaborative activities. The ADDIE model offers a systematic framework for designing, developing, and evaluating AI-supported learning strategies, ensuring continuous refinement. Findings reveal that ChatGPT significantly enhances teamwork, problem-solving, and engagement in structured group activities. However, challenges such as ethical considerations, accessibility, and AI biases must be addressed. This study contributes by proposing a replicable AI-integration model, offering guidelines for policymakers and educators, and emphasizing responsible AI use. Future research should refine AI applications for inclusivity and ethical implementation in diverse educational settings.